Muhammad Asad’s Legal Thought: A Study of His Political Theory of Islamic State - Amir, Ahmad Nabil; Rahman2, Tasnim Abdul (Universitas Muhammadiyah Yogyakarta, 2024)
The paper attempts to highlight Muhammad Asad’s epistemological postulate as reflected in his groundbreaking works pertaining to the principle of Islamic governance and its basic constitution and foundational structure. In this regard, he formulated the constitutional ideas of Islamic state whose constitution contains the provision of Islamic law that practiced and implemented the norms and postulate of the Divine Writ. This idea was partly enshrined in the Pakistan constitutional law whose political establishment was formed in 1947. It essentially discussed Muhammad Asad’s political ideas and its underlying philosophy as espoused in his works. The work conducted using qualitative approaches of the type of library research. The data were analysed by way of descriptive, analytical and comparative technique. The finding shows that Muhammad Asad had formulated comprehensive theoretical framework of legal aspect of Islamic governance drawn up from the fundamental principle and doctrine of the shariah, and its moral norms deriving from Qur’anic and the sunnah bases, while advocating democratic ideals and principles based on conventional practice and requirement of modern context of nation state.